China Internet Development Report 2017 Translated by Peng Ping - Chinese Academy of Cyberspace Studies (Springer Berlin Heidelberg : Imprint: Springer, 2019)
This book provides a comprehensive review of China's Internet development in the past 23 years since the country's first access to the Internet, especially since the 18th National Congress of the Communist Party of China. It offers a systematic account of China's experience in Internet development and governance, and establishes and presents China's Internet Development Index System, covering network infrastructure, information technology, digital economy, e-governance, cyber security, and international cyberspace governance.